2005
DOI: 10.1021/jp046060z
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Photolysis of CH2I2in Methanol:  O−H Insertion and HI Elimination Reactions To Form a Dimethoxymethane Product

Abstract: Ultraviolet photolysis of low concentrations of CH2I2 in methanol solution found that CH2I2 is converted into dimethoxymethane and some H+ and I- products. Picosecond time-resolved resonance Raman (ps-TR3) experiments observed that the isodiiodomethane (CH2I-I) photoproduct decayed faster as the concentration of methanol increases, suggesting that isodiiodomethane is reacting with methanol. Ab initio calculations indicate isodiiodomethane is able to react with methanol via an O-H insertion/HI elimination to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…The observed decay is analogous to the behavior of the iso-CH 2 I-I isomer of a structurally related CH 2 I 2 molecule. The lifetime of iso-CH 2 I-I in CH 3 CN and C 6 H 14 solutions is at least 70 times longer (0.25 and 8 ms, respectively [7,14] ) than that in CH 3 OH (3.7-5 ns [7,22] ). UV photolysis of CH 2 I 2 in CH 3 OH indicated that CH 2 I 2 is converted into CH 3 -O-CH 2 -O-CH 3 and some H + and I À products.…”
Section: Mp2 Calculationsmentioning
confidence: 90%
See 2 more Smart Citations
“…The observed decay is analogous to the behavior of the iso-CH 2 I-I isomer of a structurally related CH 2 I 2 molecule. The lifetime of iso-CH 2 I-I in CH 3 CN and C 6 H 14 solutions is at least 70 times longer (0.25 and 8 ms, respectively [7,14] ) than that in CH 3 OH (3.7-5 ns [7,22] ). UV photolysis of CH 2 I 2 in CH 3 OH indicated that CH 2 I 2 is converted into CH 3 -O-CH 2 -O-CH 3 and some H + and I À products.…”
Section: Mp2 Calculationsmentioning
confidence: 90%
“…UV photolysis of CH 2 I 2 in CH 3 OH indicated that CH 2 I 2 is converted into CH 3 -O-CH 2 -O-CH 3 and some H + and I À products. [22] Ps-TR 3 experiments showed that the iso-CH 2 I-I photoproduct decays faster as the relative concentration of methanol increases, which suggests that iso-CH 2 I-I reacts with CH 3 OH. [23] Ab initio calculations provide further support by showing that iso-CH 2 I-I reacts with CH 3 OH via an O-H insertion/HI elimination to form an iodoether (ICH 2 -O-CH 3 ) product and an HI leaving group.…”
Section: Mp2 Calculationsmentioning
confidence: 98%
See 1 more Smart Citation
“…Here, photolysis is known to lead to facile production of the iso-halomethanes following geminate recombination of the initially formed radical pair in the solvent cage, and the isomers have been shown to play a pivotal role in the reactivity of halomethanes in solution. [40][41][42][43][44][45][46][47][48][49][50][51][52][53] For example, iso-CH 2 I 2 is the primary species responsible for the FIG. 1.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 Many experimental and theoretical studies of these species have since been carried out, which illustrate novel chemistry for the isopolyhalomethanes. [35][36][37][38][39][40][41][42][43][44][45][46] For example, iso-CH 2 I 2 is the primary species responsible for the cyclopropanation of olefins when CH 2 I 2 is photolyzed in the presence of olefins. 37 In Maier's work, a number of possible resonance structures for the iso-CH 2 XY halons were considered.…”
Section: Introductionmentioning
confidence: 99%